2008
DOI: 10.1007/bf03326032
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of benzene by non-thermal plasma processing: Photocatalyst and ozone effect

Abstract: Plasma technology has some shortcomings, such as higher energy consumption and byproducts produced in the reaction process. However non-thermal plasma associated with catalyst can resolve these problems. Therefore this kind of technology was paied more and more attention to treat waste gas. A hybrid system comprising a non-thermal plasma reactor and nanometer titanium dioxide catalyst was used for benzene removal in the air. The paper described the synergistic effect of ozone and photocatalyst in the plasma re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 21 publications
2
42
0
1
Order By: Relevance
“…Ozone concentration was 300 and 320 ppm at SIE of 170 J/l in dry air and decreased to 80 ppm in humid air for MnO x /SMF and there was no change in TiO 2 /SMF electrode. It has also been shown that water vapor decreases the formation of CO and enhances the selectivity towards CO 2 (Song et al 2007;Zhu et al 2008;Karuppiah et al 2012). In DBD reactor, catalytic ozonation will play a minor role due to the inhibition of ozone formation by water vapor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ozone concentration was 300 and 320 ppm at SIE of 170 J/l in dry air and decreased to 80 ppm in humid air for MnO x /SMF and there was no change in TiO 2 /SMF electrode. It has also been shown that water vapor decreases the formation of CO and enhances the selectivity towards CO 2 (Song et al 2007;Zhu et al 2008;Karuppiah et al 2012). In DBD reactor, catalytic ozonation will play a minor role due to the inhibition of ozone formation by water vapor.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have reported non-thermal plasma (NTP) chemical processing as an effective tool for the removal of volatile organic compounds (VOCs) from gas stream. The abatement of VOCs under dilute concentrations (\1,000 ppm) may not be economical with conventional technologies such as adsorption on activated carbon, catalytic oxidation, and thermal oxidation (Subrahmanyam et al 2006a;Chorria et al 2007;Demeestere et al 2007;Zhu et al 2008: Li andGong 2010). NTP generated by electrical discharges under ambient conditions has specific advantages like mild operating conditions and may generate strong oxidizing agents like ozone, hydroxyl radical, H 2 O 2 , as well as UV light (Demeestere et al 2007;Demidyuk and Whitehead 2007;Magureanu et al 2008;Sugasawa et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 20 years, biologic process, photocatalysis process and plasma technology have been considered as methods for removal of volatile organic compounds (VOCs) and chlorinated volatile organic compounds (CVOCs) (Subrahmanyam et al 2007a, b;Zhu et al 2008). Non-thermal (non-equilibrium) plasma (NTP) has been more taken into account for VOCs degradation because it creates a very strong radical and oxidant agents degrading VOC molecules in ambient pressure and temperature (Magureanu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that increasing the residence time of pollutants in plasma reactor without changing the size of the reactor and transferring the byproducts toward reoxidation are appropriate options for increasing efficiency (Subrahmanyam et al 2006). In recent years, many researchers have investigated the combination of NTP with photocatalytic oxidation (PCO); they have reported that this system has a synergistic effect (Huang and Ye 2009;Lu et al 2012;Maciuca et al 2012;Sun et al 2007;Thevenet et al 2007;Zhu et al 2008). In this system, the activation of catalyst is attributed to the light emitted and active species created by the plasma.…”
Section: Introductionmentioning
confidence: 99%